A non-functional 5′ ALK fusion validated at the RNA level as a classical EML4-ALK that responds well to the novel ALK inhibitor ensartinib: A case report - Yang, Hong; Li, Haojing; Fang, Yu; Li, Zhijun; Zhu, Jianhua; Liu, Huan; Lu, Chao; Zhang, Xiaoyan; Ma, Tonghui; Zhang, Cuiying (Frontiers in Medicine, 2022)
Background Currently, many targeted drugs are approved for treatment of ALK fusion non-small cell lung cancer. However, it has been previously assumed that patients with 5′ non-oncogenic kinase (5′ NOK) fusion detected by DNA next-generation sequencing (NGS) would not benefit from ALK inhibitors because of lack of an intact kinase domain. Case description A novel 5′ NOK fusion form, ALK-CYP27C1 (A19:C5), was detected by DNA NGS in surgical tissue specimens of a patient with recurrent lung adenosquamous carcinoma. The patient achieved 29 months of progression-free survival with ensartinib treatment. The results of RNA NGS from the same operative tissue identified EML4-ALK (E13:A20) fusion variant type I. Conclusion This is the first case to provide real-world evidence of effective treatment of a patient with the 5′ NOK fusion form at the DNA level but functional EML4-ALK at the RNA level, illustrating the need for RNA testing in 5′ NOK patients.